Lead optimization of 8-(methylamino)-2-oxo-1, 2-dihydroquinolines as bacterial type II topoisomerase inhibitors. Issue 22 (15th November 2020) - Ushiyama, Fumihito; Amada, Hideaki; Mihara, Yasuhiro; Takeuchi, Tomoki; Tanaka-Yamamoto, Nozomi; Mima, Masashi; Kamitani, Masafumi; Wada, Reiko; Tamura, Yunoshin; Endo, Mayumi; Masuko, Aiko; Takata, Iichiro; et al.
Graphical abstract: Abstract: The global increase in multidrug-resistant pathogens has caused severe problems in the treatment of infections. To overcome these difficulties, the advent of a new chemical class of antibacterial drug is eagerly desired. We aimed at creating novel antibacterial agents against bacterial type II topoisomerases, which are well-validated targets. TP0480066 (compound 32 ) has been identified by using structure-based optimization originated from lead compound 1, which was obtained as a result of our previous lead identification studies. The MIC90 values of TP0480066 against methicillin-resistant Staphylococcus aureus (MRSA), vancomycin-resistant Enterococci (VRE), and genotype penicillin-resistant Streptococcus pneumoniae (gPRSP) were 0.25, 0.015, and 0.06 μg/mL, respectively. Hence, TP0480066 can be regarded as a promising antibacterial drug candidate of this chemical class.